Brazil 1950-1980: Three decades of growth-oriented economic policies - Pedro Malan; Régis Bonelli (Institute for Applied Economic Research (ipea), 2015)
This paper, written as a tribute to Albert Hirschman's work and thought, deals with the patterns of structural change and financing economic growth in Brazil from 1950 to 1980. Special attention in given to the role of external finance and to the evolving forms of public sector intervention. Intersectoral income shifts provoked both by inflation and economic policy measures are recognized as a key element in a growth process frequently constrained by unfavorable external events. The paper shows that concerns with the disappearance of the external and internal financing capacity of the public sector were recurrent in our economic history. The result has often been that the government lost the capability of being a coordinating element for a new growth strategy. This challenge has been faced and overcome more than once in the past, something which will have to be tried again if the Brazilian society wishes to consolidate both democracy and a just and healthy economic system.
Keywords: 330